'The influence of geography on the development of early Rome' : a thesis submitted in partial fulfilment of the requirements for a Master of Arts in History; School of Humanities at Massey University, Manawatu, New Zealand - Putt, Matthew Karl (Massey University, 2018)
Geography was an influential factor in the development of the site and city of Rome, affecting both the city itself, and the wider region. Rome was situated in a favorable position on the western cost of the Italian peninsula, with a rich hinterland consisting of volcanic soils fed by high annual rainfall, and a temperate climate. As the city was built on the intersection of two important trade routes, its people had both access to, and some control over, the natural resources of the area. These routes included Via Salaria which transported salt inland from the coast, and the main route north-south along the peninsula which linked the Etruscan tribes in the north with the Greek colonies in Campania. The Tiber River which ran along the northern edge of the city also provided a sea route to trading partners, as well as linking the city to the hinterland upstream. This interaction with close neighbours also introduced new ideas and resources which shaped the direction in which the city developed. The influence of geography cannot be overlooked in any discussion of the development of early Rome, as this was the main factor in the establishment of the early city. The availability of natural resources and key geographical features such as the Tiber River, fertile hinterland, and fresh spring-fed water supply influenced where Rome was situated. Within the location of Rome the river, hills, and valleys all dictated the spatial settlement patterns which affected the layout of the city throughout its history. These geographical features, and the Romans’ interactions with them, affected all aspects of their daily life, from providing the physical building blocks of the city, to the constant risk from natural hazards such as flooding, and also led to the need constantly to modify their environment over time, to meet the needs of a growing city.--From Conclusion
Keywords: Rome (Italy); Geography; History